1977
DOI: 10.1021/ja00454a046
|View full text |Cite
|
Sign up to set email alerts
|

Highly reactive transition metal powders. Oxidative insertion of nickel, palladium, and platinum metal powders into aryl-halide bonds

Abstract: Mass.Hydrogen removal has been shown to be at least partially rate determining in the reaction of MA0 with substrates: 8. Belleau and J. Moran, Ann. N. Y. Acad. Sci., 107, 822 (1963). The quaternary salts 10, 11, and 12 were prepared from the reaction of the corresponding unsaturated bromides or mesylate with trimethylamine. Solubilization of 10 in neutral deuterium oxide (25 'C) leads instantaneously (on the NMR time scale) to exchange of the terminal, acetylenic proton. The overwhelming preference for remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Utilization of [( p -MeOC 6 H 4 ) 3 P] 4 Pd absorbed on Celite gave a lower yield (Table , entry 6), while use of PdCl 2 (PPh 3 ) 2 (5 mol %)/CuCN (10 mol %) gave 57% yield (Table , entry 7; 20% yield with bromobenzene 15 ) of 5 . In an effort to produce a more reactive palladium catalyst, a PdCl 2 /CuCN/P, As, or Sb ligand mixture was reduced with K metal to afford activated Pd(0) . This active Pd(0) catalyst gave no coupled product in the absence of added phosphine ligands (Table , entry 8).…”
Section: Resultsmentioning
confidence: 99%
“…Utilization of [( p -MeOC 6 H 4 ) 3 P] 4 Pd absorbed on Celite gave a lower yield (Table , entry 6), while use of PdCl 2 (PPh 3 ) 2 (5 mol %)/CuCN (10 mol %) gave 57% yield (Table , entry 7; 20% yield with bromobenzene 15 ) of 5 . In an effort to produce a more reactive palladium catalyst, a PdCl 2 /CuCN/P, As, or Sb ligand mixture was reduced with K metal to afford activated Pd(0) . This active Pd(0) catalyst gave no coupled product in the absence of added phosphine ligands (Table , entry 8).…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary to Zn 0 - or hydride-mediated reduction of Ni II , Rieke and co-workers demonstrated that reduction of Ni II I 2 with potassium or lithium metal in the presence of PEt 3 produced a highly active fine metal powder, “Rieke nickel”. Treatment of this powder with bromopentafluorobenzene resulted in the formation of an isolable trans -haloaryl Ni II complex, BrNi II (PEt 3 ) 2 C 6 F 5 , in 60% yield .…”
Section: Nickel-catalyzed Reactions Of Aryl and Vinyl Sulfonates And ...mentioning
confidence: 99%
“…This turned out to be particularly true in the case of the transition metals Pt, Ni, and Pd. 26 Initially we tried the standard approach of reduction of N1I2, NiBr2, or NiCl2 with potassium in refluxing THF. Finely divided black nickel powders were obtained; however, they showed rather limited reactivity toward oxidative addition to carbon-halogen bonds.…”
Section: Activated Thalliummentioning
confidence: 99%